The influence of Peer Tutoring On Self Confidence and Mathematical Communication of Students on the Material Function - Khairul Azhar; Suci Ananda; Joni Wilson Sitopu; Amin Harahap (CV. AFDIFAL MAJU BERKAH, 2021)
This study aims to Determine (1) whether Peer Tutoring directly affect the Self Confidence of the students of SMA N I Rantau Selamat (2) whether Peer Tutoring has a direct effect on the Ability of Mathematical Communication Students of SMA N I Rantau Selamat (3) what is the Self Confidence a direct effect on the Ability of Mathematical Communication Students of SMA N I Rantau Selamat (4) what is Peer Tutoring influence on Mathematical Communication Skills of Students through Self Confidence (as an intervening) in students of SMA N I Rantau Selamat. This research is a quantitative research using the instrument test to get the value of mathematical communication of students and instruments in the form of a questionnaire to obtain data of peer tutoring and self confidence. The population in this research is students of class X SMA N I Rantau Selamat and sample in this research as many as 19 people with sampling through purposive sampling. Tool of data analysis in this research using the help of IBM SPSS 20. The method of analysis used is descriptive analysis, classical assumption test (normality test and heteroscedasticity test), and path analysis. Based on the analysis of the research, it can be concluded (1) the learning model of peer tutoring has a positive effect but not significant to the self confidence of students (2) learning model of peer tutoring has a positive effect and significant impact on mathematical communication (3) self-confidence has a positive effect but not significant to the mathematical communication (4) Self Confidence can not mediate the effect of Peer Tutoring on Mathematical Communication.